2007
DOI: 10.1053/j.gastro.2006.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism of Toll-Like Receptor 4 Gene Increases Risk of Gastric Carcinoma and Its Precursors

Abstract: Our data suggest that the TLR4+896A>G polymorphism is a risk factor for noncardia gastric carcinoma and its precursors. The findings underscore the role of the host innate immune response in outcome of H pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
198
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(206 citation statements)
references
References 40 publications
3
198
2
3
Order By: Relevance
“…TLR2 and TLR4 have been demonstrated to be important for the homeostasis of intestinal epithelial cells (39), and polymorphisms of TLR2 and TLR4 have been shown to be associated with an increased risk of gastric cancer (40,41). Accordingly, TLR2 or TLR4 are important candidates for responsible TLRs in gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 and TLR4 have been demonstrated to be important for the homeostasis of intestinal epithelial cells (39), and polymorphisms of TLR2 and TLR4 have been shown to be associated with an increased risk of gastric cancer (40,41). Accordingly, TLR2 or TLR4 are important candidates for responsible TLRs in gastric tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen percent of gastric cancer patients in the initial study and 15% of the non-cardia gastric cancer patients in the replication study had one or two TLR4 variant alleles vs 8% of both control populations (combined OR ¼ 2.4; 95% CI ¼ 1.6-3.4) (Hold et al, 2007). In contrast, prevalence of TLR4 þ 896G was not significantly increased in oesophageal squamous cell (2%, OR ¼ 0.4) or adenocarcinoma (9%, OR ¼ 0.8) or gastric cardia cancer (11%, OR ¼ 1.2) (Hold et al, 2007).…”
Section: H Pylori-induced Gastric Cancer Modelmentioning
confidence: 95%
“…TLR4 þ 896G carriers had a 7.7-fold (95% CI, 1.6-37.6) increased odds ratio (OR) for hypochlorhydria; the polymorphism was not associated with gastric acid output in the absence of H. pylori infection. Carriers also had significantly more severe gastric atrophy and inflammation (Hold et al, 2007). Sixteen percent of gastric cancer patients in the initial study and 15% of the non-cardia gastric cancer patients in the replication study had one or two TLR4 variant alleles vs 8% of both control populations (combined OR ¼ 2.4; 95% CI ¼ 1.6-3.4) (Hold et al, 2007).…”
Section: H Pylori-induced Gastric Cancer Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous study has suggested that TLR4 Asp299Gly was associated with GC in Caucasians (26); but this polymorphism was not detected in Chinese patients (27)(28)(29). Moreover, although genetic polymorphisms of TLR5 have been characterized in the Caucasian population, no study was reported on its relationship with cancer susceptibility.…”
Section: Introductionmentioning
confidence: 95%